Association of Geriatric Depression with Biosocial Factors and Malnutrition in Rural Areas of District Gautam Budh Nagar, Uttar Pradesh: A Community-Based Study - Amit Singh Pawaiya; Neha Tyagi; Ambren Chauhan; Neha Priya; Khushboo Juneja; Sachin Nagar; Shivam Bhatia (Medsci Publications, 2024)
Background: Aging mainly affects human appetite, food intake, and body weight. Physiological and psychopharmacological pathways demonstrate variations in hunger. Bodily signs characterize Elderly Depression, altered eating and sleeping patterns, cognitive impairments, and low mood. Objectives: To study the prevalence of Depression and Malnutrition in the geriatric population in the rural community and to examine the association between them among the study population. Methods: A community-based cross-sectional study was conducted in the rural areas of district Gautam Budh Nagar among geriatric population using a pre-designed pretested semi-structured questionnaire. Results: In the study, the prevalence of Depression among the study participants was found to be 155(41.2%) and malnutrition was found to be in 67 (17.8 %). Among bio social characters Age (p-value-0.000), gender (p-value-0.012), marital status (p-value-0.026), physical activity (p-value-0.004), and Malnutrition (p-value-0.000) found to be significantly associated with Depression among elderly. On multiple logistic regression, physical activity [aOR 23.6; 95% CI: 11.4-48.8] and Malnutrition or its risk [aOR 0.272; 95% CI: 0.130-0.569] were significantly associated with Geriatric Depression. Conclusions: Depression is recognized to have a significant impact on nutritional health in the elderly and is a major factor in weight loss.